2001
DOI: 10.1159/000047699
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Prognostic Models in Patients with Acute Stroke

Abstract: Prognostic models in stroke may be useful in clinical practice and research. We systematically reviewed the methodology and results of studies that have identified independent predictors of survival, independence in activities of daily living, and getting home in patients with acute stroke. Eligible studies (published in full in English) included at least 100 patients in whom at least 3 predictor variables were assessed within 30 days of stroke onset and who were followed up for at least 30 days. We recorded 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
211
0
19

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(239 citation statements)
references
References 77 publications
9
211
0
19
Order By: Relevance
“…Common approaches include dichotomizing at the median value or choosing an optimal cutoff point based on minimizing a P value. Regardless of the approach used, the practice of artificially treating a continuous risk predictor as categorical should be avoided [23,24]; yet, this is often done in the development of risk prediction models [22,[24][25][26][27]. In this review, 86 % of studies were identified that all or some continuous risk predictors were dichotomized or categorized.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…Common approaches include dichotomizing at the median value or choosing an optimal cutoff point based on minimizing a P value. Regardless of the approach used, the practice of artificially treating a continuous risk predictor as categorical should be avoided [23,24]; yet, this is often done in the development of risk prediction models [22,[24][25][26][27]. In this review, 86 % of studies were identified that all or some continuous risk predictors were dichotomized or categorized.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…This year plays a significant role in the long run (Counsell & Dennis, 2001;Kwakkel, et al, 1996;Dombovy, et al, 1986;Jongbloed, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…A number of systemic studies have shown that the factors for restoring the ability to walk and carry out daily activities are related to improving functional independence (Kwakkel, et al, 1996;Mejer, et al, 2003;Dombovy, et al, 1986;Jongbloed, 1986;Counsell & Dennis, 2001). The importance of these studies is illustrated by the fact that more than a hundred studies have been published since 1950 (Kwakkel, et al, 1996;Kwakkel,1998;Dombovy, et al, 1986;Jongbloed, 1986;Shan, et al, 1990;Feigenson, 1979;Gresham, 1990).…”
mentioning
confidence: 99%
See 2 more Smart Citations